APLIKASI PRAKIRAAN CUACA WILAYAH BALI BERBASIS ANDROID - Wipradnyana, Pande Gede; Arsa Suyadnya, I Made; Ary Esta Dewi Wirastuti, Ni Made (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i02.p02, 2018)
Weather forecast information is very important for tourism in Indonesia, especially Bali as one of the main tourist destinations. That information must be easily accessible by the users, as one of them through a mobile phone. In this research developed an application to showing the city weather forecast information and area tourist weather forecast information in Bali through mobile devices based on android operating system. The data sourced from Indonesian Agency for Meteorological, Climatological and Geophysics (BMKG). Generally, the system is divided into two parts, such as the server and client (user). Admin created in the form of web server by using HTML, PHP and JavaScript that used for the management of weather forecast data and convert data from Indonesian Agency for Meteorological, Climatological and Geophysics (BMKG), while on the client side is an application based on adroid to access the weather forecast data. In the design of the application, the planning begins with the analysis of system requirements, the implementation of coding until testing applications. The result of this research is an application of the city weather forecast information and area tourist weather forecast information in Bali which can be displayed on the mobile devices based on android operating system. Based on the result of the application testing with black box method overall funcional application has been running well.